Relationship of cultural values to counterproductive work behaviour: The mediating role of job stress - Chuchai Smithikrai (2018)
The purposes of this study were to investigate how cultural values are related to counterproductive work behaviour (CWB), and to examine whether individuals' job stress acts as a mediator between cultural types and CWB. Using an anonymous questionnaire survey, the sample was comprised of 440 employees working in government institutes and private sectors in Thailand. The results show that job stress not only has a direct relationship to CWB, but also partially mediates the relationship between cultural values and CWB. The strong mediating links were between horizontal collectivism and CWB and between vertical individualism and CWB. © 2014 Wiley Publishing Asia Pty Ltd with the Asian Association of Social Psychology and the Japanese Group Dynamics Association.